Modelling international travel as risk of acquiring Dientamoeba fragilis: Comparison to Giardia duodenalis data - Jukka-Pekka Pietilä; Tuuve A Häkkinen; Jukka Ollgren; Anu Kantele (Travel Medicine and Infectious Disease)
Background: The intestinal parasite Dientamoeba fragilis (DF) is spread worldwide and can cause prolonged gastrointestinal symptoms, yet its link to international travel has been scarcely studied. To explore this connection, we examined the association between DF cases and international travel history by destination, comparing the findings to data on Giardia duodenalis (GD), a common travel-acquired intestinal parasite. Methods: We analysed clinical data from patients with DF or GD infection in the Helsinki Metropolitan Area, categorizing the patients as travellers and non-travellers on the basis of their travel history. To assess acquisition risk by destination, we devised a DF/GD risk score (RS) relating case numbers to travel volumes as denominators in each destination, with travel data retrieved from the Official Statistics of Finland (OSF). Results: Travel history was reported less frequently by patients with DF (30 %) than GD (60 %). DF had the highest RSs for Africa (41.3), followed by Asia and Oceania (17.9) and the Americas (11.5). The respective GD RSs were 32.8, 25.4, and 11.9. The lowest RSs for both parasites were recorded for Eastern and Western Europe, Russia and the Baltic countries, and Scandinavia. For Asia and Oceania, the GD RS exceeded that of DF; for the other sites, DF had higher RSs than GD. Conclusions: Dientamoeba fragilis appears to be transmitted both domestically and internationally. Although the overall acquisition risk appears low, for both Dientamoeba fragilis and Giardia duodenalis, the highest RSs are linked to visits to (sub)tropical regions, with subregional differences between the two parasites.